Effect of delaying sporulation by addition of ammonium sulphate on the fermentation of palm kernal cake based substrate by Aspergillus niger - Swe, K. H.; Alimon, Abdul Razak; Mohammad Ismail, Mohamad Ramin (Science Publications, 2009)
Problem statement: Asexual sporulation is a common reproductive mode for a diverse group of fungi and the ultimate limiting factor in fungal biomass production. Approach: Delaying sporulation may increase the biomass in terms of mycelial production and the same time increase production of enzymes. Results: In order to delay the sporulation different levels of ammonium sulphate (10, 12 and 14%) were added in culture media as nitrogen source for fungus. It was observed that addition of 14% ammonium sulphate was the best concentration to add in culture during Solid State Fermentation (SSF) of substrate (Palm Kernel Cake (PKC) + Rice Bran) by Aspergillus niger to delay sporulation. Adding ammonium sulphate also increased the digestibility of fiber in the Fermented Substrate (FS). In addition very low sporulation was observed even after 72 h of fermentation. The development of spore forming was inhibited or delayed when ammonium sulphate was added compared to the control. Similarly, both NDF and ADF content of FS were decreased in the treatment groups. The higher the ammonium sulphate added to the medium, the lower the NDF and ADF contents of FS although the differences of NDF content were not significant after 3 days or 4 days fermentation. Conclusion/Recommendations: It was concluded that adding 14% ammonium sulphate significantly delayed sporulation and increased fungal biomass production in a solid state fermentation system.